From policing to pedagogy: Governance, mechanisms, and outcomes of school, police partnerships in character education a PRISMA guided review - Evi Nurhidayati; Nurul Astuti Yensy; Sudarwan Danim (CV. FOUNDAE, 2026)
Background: Character education has become a major educational priority in Indonesia, encouraging secondary schools to collaborate with police institutions and community stakeholders to strengthen discipline, safety, and civic values. Nevertheless, evidence on how school–police partnerships (SPPs) operate and influence character education remains limited and dispersed. Aims: This PRISMA-guided review investigates the governance models, implementation mechanisms, outcomes, and contextual factors associated with SPPs in character education. Methods: The review analyzed studies published between 2021 and 2025 focusing primarily on Indonesian secondary schools, with several regional comparisons included where relevant. Literature was identified through major academic databases, screened in two stages following PRISMA procedures, and synthesized using thematic narrative analysis. Results: The findings show that partnerships supported by formal governance arrangements, such as memoranda of understanding, operational guidelines, joint training, and restorative referral systems, tend to achieve stronger implementation and more positive school climates than informal initiatives. Interventions emphasizing mentoring, dialogue, service learning, habituation, and culturally grounded activities were associated with improvements in prosocial behavior, civic responsibility, and student discipline. Program effectiveness was influenced by school climate, parental participation, community trust, and cultural compatibility. However, inconsistencies remain in reporting validity, implementation fidelity, adaptation processes, and program costs. Conclusion: SPPs are more effective when governance, pedagogy, and restorative principles are integrated within local educational contexts. Further longitudinal and realist-oriented studies are needed to strengthen the evidence base and improve policy applicability.